ANALISIS PENERAPAN ACTIVITY BASED COSTING SEBGAI DASAR MENENTUKAN HARGA SEWA PENGINAPAN HOMESTAY DI DESA GUNUNG PADANG CIANJUR, JAWA BARAT - Danuarta, Gunawan Danu; Prijanto, Budi (Jurnal Akuntansi Syariah (JAkSya), 2024)
The Activity Based Costing method is a method that applies cost accounting concepts to determine prices more relevant and accurate. This study aims to determine the comparison of the cost of homestay rooms using traditional accounting system methods and Activity Based Costing at Homestays in Gunung Padang Village. The analysis method used is a descriptive method, namely analyzing the cost of homestay rooms in 2022, then determining the cost method based on activity-based coasting, then comparing with the previous cost of rooms set by homestay owners with the traditional system. The results showed that the calculation of the cost of rooms using the activity-based coasting method was smaller for public room types resulting in Rp. 65,749, with a difference of Rp. 2,925. and for exclusive rooms of Rp. 162,875, with a difference of Rp. 45,699. When compared to the cost of rooms that have been used previously by the homestay, this is because the homestay only uses components of costs that are considered important, while for the Activity Based Costing method by allocating activity costs to each room appropriately based on the consumption of each activity.Keywords: Activity Based Costing; Cost of Rooms; Homestay